Wheat leaf rust fungus effector Pt13024 is avirulent to TcLr30 - Qi, Yue; Li, Jianyuan; Mapuranga, Johannes; Zhang, Na; Chang, Jiaying; Shen, Qianhua; Zhang, Yue; Wei, Jie; Cui, Liping; Liu, Daqun; Yang, Wenxiang (Frontiers in Plant Science, 2023)
Wheat leaf rust, caused by Puccinia triticina Eriks. (Pt), is a global wheat disease threatening wheat production. Dissecting how Pt effector proteins interacts with wheat has great significance in understanding the pathogenic mechanism of Pt. Pt13024 was identified as a candidate effector from the differential expression transcriptome of Pt race THSN (13-5-72) interacted with susceptible cultivar Thatcher. It has the ability to inhibit cell death induced by BAX from mice and INF1 from Phytophthora infestans on Nicotiana benthamiana, and can also inhibit cell death induced by DC3000 on wheat. The 22–41 amino acids at N-terminal of the Pt13024 plays critical role in inhibiting PCD induced by BAX. Subcellular location demonstrated that Pt13024 and GFP fusion expression were localized in the cytoplasm and nucleus of the N. benthamiana cell. Reactive oxygen species and callose were detected and found that the accumulation of reactive oxygen species and deposition of callose in TcLr30 induced by Pt13024 were higher than that in 42 wheat leaf rust resistance near-isogenic lines (monogenic lines) with different resistance gene and Thatcher. HIGS was conducted and silencing Pt13024 caused Lr30 lost leaf rust resistance during the interaction between avirulent Pt race and TcLr30. We can conclude that Pt13024 plays an avirulent role to TcLr30 when Pt interacted with TcLr30. These results lay a foundation for further revealing the role of the effector protein in pathogenesis and its regulatory mechanisms.